2021
DOI: 10.55133/eji.280115
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a CD4+CD25+ Foxp3+T cells subset in Egyptian Colorectal Cancer Patients

Abstract: Human tumors including colorectal cancers (CRC) are often infiltrated by immune cells predominantly T lymphocytes especially regulatory T (Treg) cells expressing the forkhead box protein 3 (Foxp3). It has been suggested that CD25+CD4+Foxp3+ regulatory T cells (Tregs) might hamper effective immunosurveillance of emerging cancer cell. The aim of this study was to measure the frequency of total CD4+CD25+ Tregs & CD4+CD25+Foxp3+ subset of Treg cells in peripheral blood of Egyptian CRC patients and their correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The possibility of using PBMCs as a CRC marker has been tested in recent years. Some lymphocytes among the PBMCs, such as CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) and monocytic myeloid-derived suppressor cells (MMDSCs), have been found to be diagnostic and prognostic indicators of CRC [ 32 , 33 ]. Ciarloni et al [ 34 ] identified a 29-gene panel expressed in PBMCs that can be used for developing a novel minimally invasive test for accurate detection of adenomatous polyps and CRC using a standard real-time PCR platform.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using PBMCs as a CRC marker has been tested in recent years. Some lymphocytes among the PBMCs, such as CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) and monocytic myeloid-derived suppressor cells (MMDSCs), have been found to be diagnostic and prognostic indicators of CRC [ 32 , 33 ]. Ciarloni et al [ 34 ] identified a 29-gene panel expressed in PBMCs that can be used for developing a novel minimally invasive test for accurate detection of adenomatous polyps and CRC using a standard real-time PCR platform.…”
Section: Discussionmentioning
confidence: 99%